2019
DOI: 10.1039/c8cs00705e
|View full text |Cite
|
Sign up to set email alerts
|

Practical use of polymer brushes in sustainable energy applications: interfacial nanoarchitectonics for high-efficiency devices

Abstract: Polymer brushes provide a new perspective from which to consider the development of energy conversion and storage devices with improved performance and efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(74 citation statements)
references
References 205 publications
1
73
0
Order By: Relevance
“…1,3 Polymer brushes have been studied theoretically and experimentally for decades to understand and tune the properties of surfaces, including, anti-fouling, low-friction, responsive functions, etc. [5][6][7][8][9][10][11][12][13] Numerous researchers have focused on studying the swelling behavior of polymer brushes as a function of the brush molecular weight or grafting density in good solvents. [14][15][16][17][18][19] Several researchers reported on degrafting of hydrophilic polymer brushes in aqueous solution 20,21 and even degrafting of hydrophobic polymers in organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Polymer brushes have been studied theoretically and experimentally for decades to understand and tune the properties of surfaces, including, anti-fouling, low-friction, responsive functions, etc. [5][6][7][8][9][10][11][12][13] Numerous researchers have focused on studying the swelling behavior of polymer brushes as a function of the brush molecular weight or grafting density in good solvents. [14][15][16][17][18][19] Several researchers reported on degrafting of hydrophilic polymer brushes in aqueous solution 20,21 and even degrafting of hydrophobic polymers in organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer brushes are assemblies of macromolecules that are tethered by one end to a surface. These macromolecular architectures bearing different functional groups along their backbones can be grafted on different surfaces, and even in constrained environments . There are two main strategies for generating polymer brushes on solid surfaces: “grafting to” and “grafting from.” In the “grafting‐to” technique, presynthesized polymers are anchored to a surface from solution.…”
Section: Functionalization Of Solid‐state Nanoporesmentioning
confidence: 99%
“…Apart from small molecules, covalent modification of ultra-thin conducting polymers onto the carbon surface is another promising way to provide fast and reversible Faradaic redox reactions. [99,100] Baek et al reported ultrathin polyaniline-grafted RGO (denoted as PANI-g-rGO) through in situ chemical oxidative grafting of aniline in the presence of oxidizing agent ( Figure 8A). Benefiting from the covalent interaction between PANI and rGO, the PANIg-rGO exhibited a room-temperature electrical conductivity as high as 8.66 S cm −1 .…”
Section: Ultra-thin Polymersmentioning
confidence: 99%